Peran Pemerintah dalam Pengembangan Objek Wisata Yendi Beach pada Kampung Yendidori Distrik Yendidori Kabupaten Biak Numfor - Djamil Hasim (Universitas Indraprasta PGRI, 2020)
The goal of tourism development is basically to improve the status of tourism from the development sub-sector to the mainstay development sector that is able to activate the economy and other related sectors. This study aims to determine the Government's Role in the Development of Yendi Beach Tourism Object in Yendidori Village, Yendidori District, Biak Numfor District. Data collection techniques used such as; observation, interview, and documentation. The analytical method used is qualitative analysis. The results showed that the role of the Tourism Office in the Development of Yendi Beach Tourism Potential Yendindori Village in Biak Numfor Regency was dominant as a motivator where the Tourism Office as a tourism stakeholder in Biak Numfor District needed its role in motivating the community, investors and tourism entrepreneurs.